Bio-based epoxy asphalt self-repairing microcapsule and use method thereof
Through bio-based epoxy asphalt self-healing microcapsules, a bio-enzyme catalytic regeneration system is used to achieve cross-scale synergistic repair of nano-scale broken molecular chains and micron-scale cracks, which solves the technical limitations of epoxy asphalt self-healing microcapsules in compatibility, sustainability and high-temperature stability, realizes multiple repairs and efficient dispersion, and extends the life of the project.
Patent Information
- Application Number
- CN202510890709.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-30
- Publication Date
- 2025-09-26
AI Technical Summary
Existing epoxy asphalt self-healing microcapsules have problems such as poor compatibility with epoxy asphalt, dependence of the triggering mechanism on crack propagation stress, insufficient sustainability, poor high-temperature stability and limited repair scale, which result in their inability to effectively repair microcracks and interface damage during long-term service, shortening the project life.
Bio-based epoxy asphalt self-healing microcapsules are used to achieve cross-scale synergistic repair of nano-scale broken molecular chains and micron-scale cracks through a bio-enzyme catalytic regeneration system. Combined with the dual triggering mechanism of environmental response and mechanical stress, bio-enzyme complexes and modified wall materials are used to ensure that the microcapsules are not destroyed during the high-temperature construction stage and to improve the release efficiency during the service stage.
It achieves multiple repair capabilities, improves the service life of epoxy asphalt, ensures that the microcapsules are not destroyed during the high-temperature construction stage, enhances the dispersibility and repair effect in the epoxy asphalt system, and meets green environmental protection requirements.
Smart Images

Figure BDA0005474865040000101 
Figure BDA0005474865040000111 
Figure BDA0005474865040000112
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of road and bridge materials, and in particular to a bio-based epoxy asphalt self-repairing microcapsule and a method for using the same. Background Art
[0002] Epoxy asphalt, due to its excellent mechanical properties, weather resistance, and fatigue resistance, has become a mainstream paving solution for roads, bridges, and tunnels. However, over long periods of service, heavy traffic loads, extreme temperature cycles, and harsh operating environments inevitably lead to microcracks and interfacial damage. If not repaired promptly, these damages will rapidly expand and lead to structural failure, significantly shortening the project's lifespan. Due to its thermosetting nature, epoxy asphalt lacks self-healing capabilities and often requires grouting. In severe cases, milling and resurfacing are even necessary, which is time-consuming and labor-intensive.
[0003] In recent years, domestic and foreign scholars have studied the self-repair of epoxy asphalt by adding microcapsules, but there are the following technical limitations: (1) Poor compatibility with epoxy asphalt. The polarity difference between traditional microcapsule wall materials and epoxy asphalt systems is large, resulting in uneven dispersion of microcapsules and easy formation of stress concentration points; (2) The triggering mechanism is overly dependent on crack propagation stress; (3) Insufficient sustainability. After the microcapsules rupture and release the repair agent, they can only be repaired once; (4) Poor high-temperature stability. The construction temperature of epoxy asphalt often reaches 160℃~180℃. Traditional microcapsule wall materials are easy to soften, deform or crack at high temperatures, losing their self-repair function; (5) Limited repair scale. The repair scale of traditional core materials is mostly limited to filling micron-level cracks and cannot repair broken nano-level molecular chains.
[0004] Therefore, the existing epoxy asphalt self-healing microcapsule solution has technical limitations and its large-scale application is restricted. There is an urgent need to develop self-healing microcapsules with sustainable repair properties to fundamentally solve the aging and cracking problems of epoxy asphalt mixtures and extend the service life of the pavement layer.
[0005] The information disclosed in this background technology section is only intended to deepen the understanding of the overall background technology of the present invention and should not be regarded as an admission or any form of suggestion that the information constitutes the prior art known to those skilled in the art. Summary of the Invention
[0006] In order to solve the above technical problems, the present invention provides a bio-based epoxy asphalt self-repairing microcapsule and a method for using the same, which realizes cross-scale synergistic repair of nano-scale broken molecular chains and micron-scale cracks of aged epoxy asphalt through a bio-enzyme catalytic regeneration system, and realizes the self-regeneration cycle of auxiliary enzymes through multiple paths to achieve multiple repairs. In addition, a dual trigger mechanism of environmental response and mechanical stress is constructed to ensure that the microcapsule is not destroyed during the construction stage, improve the release efficiency during the service stage, and improve the core material repair effect.
[0007] The first object of the present invention is to provide a bio-based epoxy asphalt self-repairing microcapsule, the self-repairing microcapsule comprising a bio-based core material and a reactive wall material;
[0008] Calculated by weight, bio-based core materials include:
[0009] 8-10 parts of repair enzyme complex;
[0010] 3-5 parts of auxiliary enzyme complex;
[0011] 20-25 parts of regeneration substrate;
[0012] 10-15 parts of protective agent;
[0013] Reactive wall materials include:
[0014] 20-25 parts of bio-based main wall materials;
[0015] 1 to 5 parts of stress inducer;
[0016] 0.5-1 part of surface modifier;
[0017] 3 to 5 parts of cross-linking agent.
[0018] As a preferred embodiment of the present invention, the repair enzyme complex is formed by mixing ether cleavage enzyme, lipase and epoxy bio-oil in a mass ratio of 1-2:1-2:10-20; the epoxy bio-oil accounts for a large proportion, and under the action of capillary force, it carries ether cleavage enzyme and lipase to the damaged area, and the ether cleavage enzyme and lipase can accurately identify the damaged site and respectively repair the ether bond and ester bond broken by aging of the epoxy resin, thereby realizing the repair of nano-scale molecular chain breaks; specifically, the serine residue in the active center of the ether cleavage enzyme attacks the CO bond at the ether bond breakage site to form an enzyme-substrate The oxidized coenzyme provides hydrogen protons to reduce the adjacent epoxy groups to hydroxyl groups, which condense with the groups at both ends of the broken ether bond to reform the ether bond. The lipase hydrolyzes the carboxylic acid at the broken site and the alcohol in the regenerated substrate to form an acyl-enzyme intermediate. The artificial coenzyme promotes the dehydration condensation of the acyl group and the alcohol to reform the ester bond. The epoxidized bio-oil penetrates into the cracks and undergoes cross-linking reactions with the reactive groups such as carboxyl, hydroxyl and carbonyl in the aged asphalt to fill the micron-scale gaps, ultimately achieving cross-scale synergistic repair of nanoscale broken molecular chains and micron-scale cracks.
[0019] Ether lyase is obtained by hydrophilic modification of thermophilic etherase;
[0020] More specifically, the modification method comprises dissolving the thermophilic etherase in sodium borate buffer (pH 8.5), dissolving activated polyethylene glycol in anhydrous dimethyl sulfoxide, slowly adding the activated polyethylene glycol solution dropwise to the thermophilic etherase solution under stirring, and reacting for 6 hours in a dark and low temperature (4-8°C) condition to obtain a hydrophilized ether lyase; during the preparation process, amino groups on the surface of the thermophilic etherase undergo a nucleophilic substitution reaction with the activated polyethylene glycol, and the hydrophilic polyethylene glycol chain is grafted onto the surface of the enzyme molecule by forming a stable amide bond;
[0021] The surface of thermophilic etherase is rich in hydrophobic groups, and its dispersibility in epoxy system can be improved by hydrophilic modification with grafted polyethylene glycol.
[0022] The lipase is derived from the Candida antarctica lipase through lipophilic modification.
[0023] More specifically, the modification method comprises dissolving antarctic Candida lipase in sodium phosphate buffer (pH 8), dissolving an activated octadecyl group in anhydrous N,N-dimethylformamide, slowly adding the activated octadecyl group solution dropwise to the antarctic Candida lipase solution under stirring, and stirring the reaction at 25° C. in the dark for 4 hours to obtain a lipophilized lipase; during the above preparation process, the nucleophilic groups on the surface of the lipase attack the electrophilic center of the activated octadecyl group, and through an SN2 nucleophilic substitution reaction, the nucleophilic groups of the enzyme protein replace the halogen to form a stable CN or CO covalent bond, so that the hydrophobic octadecyl chain is firmly grafted to the surface of the enzyme molecule;
[0024] The surface of Antarctic Candida lipase is hydrophilic. Octadecyl lipophilic modification can improve its uniform distribution in the asphalt phase and interfacial contact with epoxidized bio-oil, thereby improving the catalytic remediation efficiency.
[0025] The melting points of ether cleavage enzymes and lipases are 150-180°C. More specifically, the mixing temperature of epoxy asphalt is usually between 150-180°C. Selecting enzymes with such melting points ensures that they are not inactivated during the mixing process.
[0026] The epoxidized bio-oil is at least one of epoxidized soybean oil, epoxidized castor oil, and epoxidized cottonseed oil. More specifically, the epoxidized bio-oil penetrates into the cracks, where the epoxy groups in the oil cross-link with reactive groups such as carboxyl, hydroxyl, and carbonyl groups in the aged asphalt, filling the micron-sized voids.
[0027] The viscosity of the epoxy bio-oil is 200mPa·s to 500mPa·s. More specifically, within this viscosity range, the epoxy bio-oil can fully penetrate and fill micron-sized voids, while ensuring that the epoxy groups fully contact and effectively cross-link with reactive groups such as carboxyl, hydroxyl, and carbonyl in the aged asphalt, thereby achieving efficient repair of cracks in the aged asphalt.
[0028] As a preferred embodiment of the present invention, the coenzyme complex is formed by mixing the oxidized coenzyme and the artificial coenzyme in a mass ratio of 3-5:5-7;
[0029] The oxidized coenzyme is at least one of nicotinamide coenzyme, flavin coenzyme and quinone coenzyme; more specifically, the oxidized coenzyme provides hydrogen protons when the ether cleavage enzyme repairs the ether bond;
[0030] The artificial coenzyme is at least one of artificial nicotinamide, phenazine methyl sulfate and artificial quinone coenzymes; more specifically, the artificial coenzyme acts as a promoter when lipase repairs ester bonds. The artificial coenzyme can optimize the binding site through specific binding to the active center of lipase, reduce the activation energy of the reaction, and significantly improve the activity and reaction rate of the enzyme.
[0031] As a preferred embodiment of the present invention, the thermal decomposition temperature of the bio-based main wall material is greater than 250°C. More specifically, the selection of wall materials with high thermal decomposition temperatures can ensure that the wall materials are not damaged in the high temperature environment during the mixing and construction stage.
[0032] The bio-based main wall material is a composite system of chitosan and nanocellulose whiskers;
[0033] More specifically, chitosan can be protonated in an alkaline environment after epoxy curing, causing the wall material to swell, increasing the pore size and improving the release efficiency of the core material. Nanocellulose whiskers, as rigid fillers, can significantly increase the rigidity of the wall material, preventing the microcapsules from prematurely rupturing due to rolling of the mixture. They also have angular structures that can act as brittle nodes, increasing the stress concentration factor and reducing the rupture stress threshold.
[0034] Preferably, the mass ratio of chitosan to nanocellulose whiskers is 4-5:0.8-1. The reason why chitosan accounts for a large proportion in the bio-based main wall material is that a sufficient amount is needed to provide the wall material with flexibility and film-forming properties. If the chitosan ratio is too low, the wall material will suffer from insufficient continuity and easy brittle cracking. The reason why nanocellulose whiskers account for a small proportion in the bio-based main wall material is that a small amount of nanocellulose whiskers can significantly improve the stiffness of the composite material. If the ratio is too high, the wall material will be too rigid and the toughness will decrease.
[0035] Chitosan is modified with methyl methacrylate and grafted with alkyl chains. More specifically, by grafting alkyl chains onto chitosan, the alkyl chains, as hydrophobic groups, can form a similar compatibility effect with the epoxy system, significantly reducing the interfacial tension between the microcapsules and the epoxy matrix, thereby preventing the microcapsules from agglomerating and settling in the epoxy system, and significantly enhancing the dispersibility of the bio-based microcapsules in the epoxy system.
[0036] The elastic moduli of chitosan and nanocellulose whiskers are 0.5GPa~1GPa and 150GPa~200GPa respectively; more specifically, chitosan, as a flexible matrix, has a lower modulus that gives the wall material excellent deformation ability, allowing it to undergo moderate elastic deformation without brittle cracking when subjected to stress, ensuring that the material has good flexibility and impact resistance; while nanocellulose whiskers act as a reinforcing skeleton with their ultra-high modulus characteristics, and their rigid structure can effectively limit excessive deformation of the matrix, significantly improving the overall stiffness and load-bearing capacity of the wall material.
[0037] As a preferred embodiment of the present invention, the stress inducing agent is at least one of nano-silicon dioxide or nano-calcium carbonate treated with a surface modifier, the content of which is 10-20wt% of the bio-based main wall material, the elastic modulus is 150GPa-200GPa, and the preset defect density is 10 4 ~10 6 pieces / cm 2 ; More specifically, the stress inducer acts as a brittle node and synergistically acts with the nanocellulose whiskers to significantly reduce the fracture stress threshold; the content range of the above-mentioned stress inducer and the preset defect density range are both intended to ensure the proportion of brittle nodes on the surface of the bio-based main wall material, so as to play a role in reducing the fracture stress threshold; the elastic modulus of the stress inducer is equivalent to that of the nanocellulose whiskers, because it avoids excessive stress concentration due to the modulus difference of the brittle nodes, resulting in too small a fracture stress.
[0038] The surface modifier is at least one of a silane coupling agent and anhydrous sorbitan oleate; more specifically, the surface modifier is used to impart active groups to the stress inducer, thereby enhancing the dispersibility of the bio-based main wall material in the epoxy system.
[0039] As a preferred embodiment of the present invention, the particle size of the self-repairing microcapsules ranges from 100 μm to 200 μm. More specifically, if the particle size of the self-repairing microcapsules is too small, not only will the reserve of the repair agent in a single microcapsule be insufficient, but it will also form dense stress concentration points, reducing the overall strength of the material. If the particle size is too large, the fracture stress is small, and it is easy to break prematurely during the mixing and construction stage.
[0040] The thickness of the reactive wall material is 1μm~2μm, and the fracture stress range is 15MPa~60MPa; more specifically, the wall thickness directly affects the fracture strength of the reactive wall material. When the thickness of the wall material is 1μm~2μm, the calculated fracture stress ranges from 15MPa~60MPa, which is slightly higher than the crack propagation stress of epoxy asphalt. Under the synergistic effect of the brittle nodes, it ensures that the crack stress can trigger fracture, and the shear force and pressure of mixing and rolling will not cause the wall material to rupture prematurely.
[0041] As a preferred embodiment of the present invention, the regeneration substrate is a mixture of glucose and ethanol in a mass ratio of 6-8:2-4; more specifically, glucose as the main substrate preferentially reacts with the inactivated coenzyme to generate a new coenzyme; ethanol as the cosubstrate can, on the one hand, provide reaction conditions for ester bond repair, and on the other hand, when the glucose is exhausted, it can also react with the inactivated coenzyme to generate a new coenzyme. At the same time, the residual aromatic components in the epoxy asphalt system and the oil components in the epoxy bio-oil can be used as supplements after the consumption of glucose, and the self-regeneration cycle of the auxiliary enzyme is realized through multiple paths, and multiple repair reactions are achieved without relying on external functions; the reason for the mass ratio of glucose to ethanol is 6-8:2-4 is that the initial high ratio of glucose can meet the rapid start-up requirements of the regeneration reaction, and the low initial ratio of ethanol can ensure the stability of the enzyme system.
[0042] As a preferred embodiment of the present invention, the protective agent is a mixture of glycerol and trehalose in a mass ratio of 2-3:1-2; more specifically, glycerol can prevent the enzyme from being inactivated due to dehydration by forming hydrogen bonds with polar groups on the surface of the enzyme molecules. Glycerol can also lower the freezing point of the core material solution to prevent the formation of ice crystals in a low-temperature environment from piercing the microcapsules or destroying the enzyme structure; trehalose forms an amorphous glassy matrix at high temperatures, which encapsulates the enzyme molecules and inhibits further thermal motion and aggregation denaturation of the enzyme molecules; the reason for the mass ratio range of 2-3:1-2 is that too low a glycerol concentration will cause the enzyme to be inactivated and destroyed under dryness or low temperature, while excessive glycerol will reduce the mechanical strength of the microcapsules; when the trehalose concentration is too low, a continuous glassy matrix cannot be formed, and when the concentration is too high, trehalose is prone to crystallization and precipitation, destroying the uniformity of the protective layer and reducing the thermal stability; in addition, at this mass ratio, glycerol and trehalose can form a "dynamic hydration-glassy" two-phase protective layer with the best protective effect.
[0043] The cross-linking agent is at least one of tea polyphenols, tannic acid or sodium tripolyphosphate; more specifically, the cross-linking agent reacts with chitosan to form the wall material. The cross-linking agent is a physical cross-linking agent or a natural adhesive, and has the advantages of mild reaction and environmental protection.
[0044] As a preferred embodiment of the present invention, the self-repairing microcapsules are formed by sequentially adding a bio-based core material solution, an emulsifier, and a cross-linking agent to a reactive wall material precursor solution, stirring the solution, and then freeze-drying the solution.
[0045] The reactive wall material precursor liquid is formed by sequentially adding a stress inducer and a surface modifier into a bio-based main wall material and stirring the mixture.
[0046] Furthermore, the preparation method of the self-repairing microcapsules is specifically as follows:
[0047] S1. Dissolve 1 g to 2 g of hydrophilized ether lyase and 1 g to 2 g of lipophilized lipase in 40 to 60 mL of deionized water, mix with 10 g to 20 g of epoxy bio-oil, and then disperse by ultrasonication for 5 to 20 minutes to form a repair enzyme mixture;
[0048] S2, mixing the repair enzyme mixture, 10g-15g of a protective agent, 3g-5g of an auxiliary enzyme complex, and 20g-25g of a regeneration substrate, and then ultrasonically dispersing the mixture for 5-20 minutes to form a bio-based core material solution;
[0049] S3, dissolving 40 g to 50 g of methyl methacrylate-modified chitosan in 300 mL of 1% acetic acid solution, stirring magnetically for 2 to 8 h until completely dissolved, adding 8 to 10 g of nanocellulose whiskers, and ultrasonically dispersing for 10 to 50 min to form a reactive wall material solution;
[0050] S4. Add 5g to 10g of stress inducing agent and 2g to 5g of surface modifier to the reactive wall material solution and continue stirring to form a reactive wall material precursor solution;
[0051] S5. Add the bio-based core material solution obtained in S2 to the reactive wall material precursor solution obtained in S4, and add 0.5 g of emulsifier at the same time. High-speed shearing is carried out at 10,000 to 20,000 rpm for 5 to 30 minutes. Then, a cross-linking agent is added dropwise, and the mixture is stirred and reacted for 1 to 5 hours. Chitosan and the cross-linking agent form a network structure to wrap the core material through ionic bonds, and the bio-based epoxy self-healing microcapsules are formed after freeze-drying.
[0052] Preferably, the freeze-drying temperature in S5 is -50°C, the pressure is 10 Pa, and the time is 24 hours. During the freeze-drying process, the protective agent forms a glassy state, which can effectively prevent the inactivation of the enzyme system.
[0053] Preferably, by controlling the shear rate and time in step S5 , the shear stress on the droplets and the sufficiency of droplet breakage can be controlled, thereby controlling the particle size and particle size distribution of the microcapsules.
[0054] A second object of the present invention is to provide a method for using bio-based epoxy asphalt self-repairing microcapsules, comprising:
[0055] The self-repairing microcapsules and the epoxy resin component A are mixed evenly to obtain a microcapsule-epoxy resin premix;
[0056] The aggregate, epoxy resin component B and asphalt are pre-mixed uniformly to obtain epoxy asphalt premix;
[0057] The microcapsule-epoxy resin premix is added into the epoxy asphalt premix and mixed to form a bio-based self-repairing microcapsule epoxy asphalt mixture.
[0058] Furthermore, a method for using bio-based epoxy asphalt self-repairing microcapsules is specifically as follows:
[0059] P1. Mix the bio-based epoxy asphalt self-repairing microcapsules and epoxy resin component A at a mass ratio of 1-2:10-15 at 40°C to form an epoxy resin-microcapsule premix;
[0060] P2. Preheat the aggregate, epoxy resin component B, and asphalt to 170°C to 180°C, 40°C to 60°C, and 150°C to 160°C, respectively. Add the epoxy resin component B and asphalt to the aggregate and mix at 160°C to 180°C for 60s to 75s to form an epoxy asphalt premix.
[0061] P3. Add the epoxy resin-microcapsule premix formed in P1 to the epoxy asphalt premix formed in P2, and quickly mix for 10s to 15s at 160°C to 180°C to form a bio-based self-healing microcapsule epoxy asphalt mixture.
[0062] Furthermore, the mass ratio of bio-based epoxy asphalt self-repairing microcapsules to epoxy resin component A is 1-2:10-15, to ensure that the proportion of microcapsules in the epoxy system is in the range of 3% to 10%; the reason for the preferred proportion range is that: a proportion of less than 3% will lead to insufficient amount of repair core material and limited repair effect; microcapsules are heterogeneous particles, and when the proportion is greater than 10%, it will destroy the continuity of the matrix, form stress concentration points, cause the mixture to become brittle, and reduce toughness.
[0063] Furthermore, the rapid mixing temperature is 160°C to 180°C, and the mixing time is 10s to 15s. High-temperature rapid mixing can not only ensure the mixing uniformity of the mixture as much as possible, but also shorten the residence time of the microcapsules at high temperatures, thereby avoiding the softening or decomposition of the wall material due to long-term heat, which may lead to premature leakage of the repair agent.
[0064] Compared with the prior art, the present invention has the following beneficial effects:
[0065] (1) The present invention develops self-repairing microcapsules suitable for epoxy asphalt based on the bio-enzyme catalytic regeneration system. The microcapsules rupture under the action of crack propagation stress and release the bio-based core material. The epoxy bio-oil therein carries ether cleavage enzymes and lipases to the damaged area under the action of capillary force. The ether cleavage enzymes and lipases can accurately identify the damaged sites. The ether cleavage enzymes and lipases respectively repair the ether bonds and ester bonds broken by aging of the epoxy resin. The serine residue in the active center of the ether cleavage enzyme attacks the CO bond at the ether bond breakage to form an enzyme-substrate intermediate. The oxidized coenzyme provides hydrogen protons to reduce the adjacent epoxy group to hydroxyl groups. The hydroxyl groups condense with the groups at both ends of the broken ether bond to reform the ether bond. The lipase hydrolyzes the carboxylic acid at the breakage with the alcohol in the regenerated substrate to form an acyl-enzyme intermediate. The artificial coenzyme promotes the dehydration condensation of the acyl group and the alcohol to reform the ester bond. The epoxy bio-oil penetrates into the cracks and undergoes cross-linking reaction with the reactive groups such as carboxyl, hydroxyl and carbonyl in the aged asphalt to fill the micron-scale gaps, ultimately achieving cross-scale synergistic repair of nano-scale broken molecular chains and micron-scale cracks.
[0066] (2) When the repair enzyme complex repairs the broken molecular chain, it needs auxiliary enzymes to provide reaction conditions. However, the auxiliary enzymes will be inactivated as the reaction proceeds, resulting in repair failure. The present invention preferably uses glucose and ethanol as regeneration substrates. When the coenzyme is inactivated, glucose as the main substrate preferentially reacts with the inactivated coenzyme to generate new coenzymes. Ethanol as a cosubstrate can, on the one hand, provide reaction conditions for ester bond repair, and on the other hand, when glucose is exhausted, it can also react with the inactivated coenzyme to generate new coenzymes. In addition, the residual aromatic components in the epoxy asphalt system and the oil components in the epoxy bio-oil can both be used as supplements after glucose consumption, and the auxiliary enzyme self-regeneration cycle is realized through multiple paths, and multiple repair reactions are achieved without relying on external functions.
[0067] (3) The present invention selects a chitosan-nanocellulose whisker composite system with a thermal decomposition temperature of >250°C as a reactive wall material to ensure that the microcapsules are not destroyed under high-temperature mixing conditions of 160°C to 180°C. Nanocellulose whiskers, as rigid fillers, can significantly improve the rigidity of the wall material. They also have an angular structure and can serve as brittle nodes to increase the stress concentration coefficient. They synergize with stress inducers to significantly reduce the fracture stress threshold. In addition, the alkaline environment after epoxy asphalt curing can trigger the protonation of chitosan amino groups, the wall material swells, and the pore size increases. Ultimately, through the dual triggering mechanism of environmental response and mechanical stress, it is ensured that the microcapsules are not destroyed during the mixing and construction stages, and the release efficiency is improved during the service stage, thereby improving the core material repair effect.
[0068] (4) The present invention modifies chitosan and stress inducer respectively by using methyl methacrylate and surface modifier, so that active groups are generated on the surface of the self-repairing microcapsule wall material, thereby improving the compatibility with the epoxy asphalt system. At the same time, during use, the microcapsules are pre-mixed with the epoxy resin A component, which not only improves the dispersibility of the microcapsules in the epoxy asphalt system, but also avoids the damage to the microcapsules caused by long-term mixing.
[0069] (5) The repair enzyme complex, protective agent, chitosan main wall material, etc. in the bio-based epoxy asphalt self-repairing microcapsules provided by the present invention are all biodegradable materials. In addition, the present invention realizes multiple cycles of self-repair based on the bio-enzyme catalytic regeneration system, and the repair product is non-toxic, meeting the needs of green environmental protection and sustainable development. DETAILED DESCRIPTION
[0070] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below.
[0071] Sources of raw materials used in the examples and comparative examples:
[0072] Ether lyase: Thermophilic etherase, Shanghai Aladdin Biochemical Technology Co., Ltd.
[0073] Lipase: Candida antarctica lipase, Shanghai Aladdin Biochemical Technology Co., Ltd.
[0074] Epoxidized bio-oil: epoxidized soybean oil, epoxidized castor oil and epoxidized cottonseed oil, 1688 Alibaba procurement and wholesale network.
[0075] Oxidized coenzymes: nicotinamide coenzyme, flavin coenzyme and quinone coenzyme, Shanghai Aladdin Biochemical Technology Co., Ltd.
[0076] Artificial coenzymes: artificial nicotinamide, phenazine methyl sulfate and artificial quinone coenzymes, Shanghai Aladdin Biochemical Technology Co., Ltd.
[0077] Regeneration substrate: glucose, ethanol, 1688 Alibaba procurement and wholesale network.
[0078] Protective agents: glycerol, trehalose, 1688 Alibaba purchasing and wholesale network.
[0079] Bio-based main wall materials: chitosan, nanocellulose whiskers, 1688 Alibaba procurement and wholesale network.
[0080] Stress inducing agents: nano-silicon dioxide, nano-calcium carbonate, 1688 Alibaba procurement and wholesale network.
[0081] Surface modifiers: silane coupling agent, sorbitan oleate, Shanghai Aladdin Biochemical Technology Co., Ltd.
[0082] Cross-linking agent: tea polyphenols, tannic acid, sodium tripolyphosphate, Shanghai Aladdin Biochemical Technology Co., Ltd.
[0083] Epoxy resin A component: E51, 1688 Alibaba procurement and wholesale network.
[0084] Epoxy resin B component: m-phenylenediamine, 1688 Alibaba procurement and wholesale network.
[0085] Aggregate: Basalt stone, 1688 Alibaba procurement and wholesale network.
[0086] Asphalt: 70# base asphalt, Sinopec Yangzi Petrochemical Co., Ltd.
[0087] Conventional chemical reagents and materials involved: deionized water, methyl methacrylate, polyethylene glycol, octadecyl, methyl methacrylate, 1% acetic acid solution, emulsifier, polyimide, Shanghai Aladdin Biochemical Technology Co., Ltd.
[0088] The preparation method of the hydrophilized ether lyase in the examples and comparative examples is:
[0089] A1. Dissolve 10 mg of thermophilic etherase in 2 mL of sodium borate buffer (pH 8.5) to obtain a thermophilic etherase solution;
[0090] A2. Dissolve 20 mg of activated polyethylene glycol in 1 mL of anhydrous dimethyl sulfoxide to obtain an activated polyethylene glycol solution;
[0091] A3. Slowly add the activated polyethylene glycol solution dropwise to the thermophilic etherase solution under stirring, ensuring that the molar ratio of enzyme to polyethylene glycol in the final solution is 1:10;
[0092] A4, react at low temperature (4-8°C) in the dark for 6 hours to obtain hydrophilic ether lyase
[0093] The preparation method of the lipophilized lipase in the examples and comparative examples is:
[0094] B1. Dissolve 10 mg of Candida antarctica lipase in 1 mL of sodium phosphate buffer (pH 8) to obtain a Candida antarctica lipase solution;
[0095] B2. Dissolve 10 mg of activated octadecyl in 0.5 mL of anhydrous N,N-dimethylformamide to obtain an activated octadecyl solution;
[0096] B3. Slowly add the activated octadecyl solution dropwise to the Candida antarctica lipase solution under stirring, ensuring that the molar ratio of enzyme to octadecyl in the final solution is 1:10;
[0097] B4. Stir and react at 25°C in the dark for 4 h to obtain lipophilic lipase.
[0098] The preparation method of the bio-based epoxy self-repairing microcapsules in the examples and comparative examples is as follows:
[0099] S1. Dissolve 1 g to 2 g of hydrophilized ether lyase and 1 g to 2 g of lipophilized lipase in 50 mL of deionized water, mix with 10 g to 20 g of epoxy bio-oil, and then disperse by ultrasonication for 10 minutes to form a repair enzyme mixture;
[0100] S2, mixing the repair enzyme mixture, 10g-15g of protective agent, 3g-5g of auxiliary enzyme complex, and 20g-25g of regeneration substrate, and then ultrasonically dispersing for 10 minutes to form a bio-based core material solution;
[0101] S3, dissolving 40 g to 50 g of methyl methacrylate-modified chitosan in 300 mL of 1% acetic acid solution, stirring magnetically for 4 h until completely dissolved, adding 8 to 10 g of nanocellulose whiskers, and ultrasonically dispersing for 30 min to form a reactive wall material solution;
[0102] S4. Add 5g to 10g of stress inducing agent and 2g to 5g of surface modifier to the reactive wall material solution and continue stirring for 1h to form a reactive wall material precursor solution;
[0103] S5. Add the bio-based core material solution obtained in S2 to the reactive wall material precursor solution obtained in S4, and add 0.5 g of emulsifier at the same time. High-speed shearing at 15,000 rpm for 10 minutes, then add the cross-linker dropwise, and react with stirring for 2 hours. Chitosan and the cross-linker form a network structure to wrap the core material through ionic bonds, and after freeze-drying, bio-based epoxy self-healing microcapsules are formed.
[0104] The preparation and testing methods of the mixtures in the examples and comparative examples refer to the "Testing Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E20-2011). The specific test and evaluation methods for the bio-based self-healing microencapsulated epoxy asphalt mixture are as follows:
[0105] A1. First, the mixture was subjected to a four-point fatigue test and a beam bending test. The four-point bending test frequency was 10 Hz and the control strain was 5 × 10 -4 The test temperature is 15℃, and the test is stopped when the initial stiffness modulus reaches 50%; the loading rate of the beam bending test is 50mm / min, and the test temperature is -10℃; and the initial stiffness, fatigue life and maximum bending strain of the beam are recorded;
[0106] A2. Place the beam specimens after the fatigue test in A1 in a -20°C and 70°C insulation box for a 2-hour interval, and then place them in a 20°C room temperature for a 4-hour interval. Perform the same four-point bending fatigue test and beam bending test again on the beams after the interval, and calculate the initial stiffness recovery rate, fatigue life recovery rate, and beam maximum bending strain recovery rate after the first repair.
[0107] A3. The beam specimens that have undergone the A2 fatigue test are tested again according to the A2 test conditions to obtain the initial stiffness recovery rate, fatigue life recovery rate, and maximum bending and tensile strain recovery rate of the beam after the second repair;
[0108] A4. The small beam specimen that has undergone the A3 fatigue test is tested again according to the A3 test conditions to obtain the initial stiffness recovery rate, fatigue life recovery rate and small beam maximum bending and tensile strain recovery rate after the third repair.
[0109] Example 1
[0110] The bio-based epoxy asphalt self-healing microcapsules provided in this embodiment are calculated by weight, and the selected bio-based core materials include 0.7 parts of ether cleavage enzyme, 0.7 parts of lipase, 6.6 parts of epoxy soybean oil, 1.2 parts of nicotinamide coenzyme, 1.8 parts of artificial nicotinamide, 15 parts of glucose, 5 parts of ethanol, 6.5 parts of glycerol and 3.5 parts of trehalose; the selected reactive wall materials include: 20 parts of chitosan-nanocellulose whiskers, 1 part of nano-silica, 0.5 parts of silane coupling agent and 3 parts of tea polyphenols.
[0111] A method for using bio-based epoxy asphalt self-repairing microcapsules is as follows:
[0112] P1. Mix the bio-based epoxy asphalt self-repairing microcapsules and epoxy resin component A at a mass ratio of 1:15 at 40°C to form an epoxy resin-microcapsule premix;
[0113] P2. Preheat the aggregate, epoxy resin component B, and asphalt to 170°C to 180°C, 40°C to 60°C, and 150°C to 160°C, respectively. Add the epoxy resin component B and asphalt to the aggregate and mix at 160°C to 180°C for 60s to 75s to form an epoxy asphalt premix.
[0114] P3. Add the epoxy resin-microcapsule premix formed in P1 to the epoxy asphalt premix formed in P2, and quickly mix for 10s to 15s at 160°C to 180°C to form a bio-based self-healing microcapsule epoxy asphalt mixture.
[0115] Example 2
[0116] The bio-based epoxy asphalt self-healing microcapsules provided in this embodiment are calculated by weight, and the selected bio-based core materials include 0.75 parts of ether cleavage enzyme, 0.75 parts of lipase, 7.5 parts of epoxy castor oil, 1.6 parts of flavin coenzyme, 2.4 parts of phenazine methyl sulfate, 16 parts of glucose, 7 parts of ethanol, 8 parts of glycerol and 5 parts of trehalose; the selected reactive wall materials include 23 parts of chitosan-nanocellulose whiskers, 3 parts of nano-silica, 0.75 parts of silane coupling agent and 4 parts of tannic acid.
[0117] A method for using bio-based epoxy asphalt self-repairing microcapsules is as follows:
[0118] P1, bio-based epoxy asphalt self-repairing microcapsules and epoxy resin component A were mixed at a mass ratio of 1.75:12.5 at 40°C to form an epoxy resin-microcapsule premix;
[0119] P2. Preheat the aggregate, epoxy resin component B, and asphalt to 170°C to 180°C, 40°C to 60°C, and 150°C to 160°C, respectively. Add the epoxy resin component B and asphalt to the aggregate and mix at 160°C to 180°C for 60s to 75s to form an epoxy asphalt premix.
[0120] P3. Add the epoxy resin-microcapsule premix formed in P1 to the epoxy asphalt premix formed in P2, and quickly mix for 10s to 15s at 160°C to 180°C to form a bio-based self-healing microcapsule epoxy asphalt mixture.
[0121] Example 3
[0122] The bio-based epoxy asphalt self-healing microcapsules provided in this embodiment are calculated by weight, and the selected bio-based core materials include 0.8 parts of ether cleavage enzyme, 0.8 parts of lipase, 8.4 parts of epoxy cottonseed oil, 2 parts of quinone coenzymes, 3 parts of artificial quinone coenzymes, 17 parts of glucose, 8 parts of ethanol, 9 parts of glycerol and 6 parts of trehalose; the selected reactive wall materials include 25 parts of chitosan-nanocellulose whiskers, 5 parts of nano-calcium carbonate, 1 part of anhydrous sorbitan oleate and 5 parts of sodium tripolyphosphate.
[0123] A method for using bio-based epoxy asphalt self-repairing microcapsules is as follows:
[0124] P1. Mix the bio-based epoxy asphalt self-repairing microcapsules and epoxy resin component A at a mass ratio of 1.5:15 at 40°C to form an epoxy resin-microcapsule premix;
[0125] P2. Preheat the aggregate, epoxy resin component B, and asphalt to 170°C to 180°C, 40°C to 60°C, and 150°C to 160°C, respectively. Add the epoxy resin component B and asphalt to the aggregate and mix at 160°C to 180°C for 60s to 75s to form an epoxy asphalt premix.
[0126] P3. Add the epoxy resin-microcapsule premix formed in P1 to the epoxy asphalt premix formed in P2, and quickly mix for 10s to 15s at 160°C to 180°C to form a bio-based self-healing microcapsule epoxy asphalt mixture.
[0127] The performance test results of Examples 1 to 3 are shown in Table 1:
[0128] Table 1 Test results of bio-based epoxy asphalt self-repairing microcapsule mixtures in Examples 1 to 3
[0129]
[0130]
[0131] Comparative Example 1
[0132] The bio-based core material used in this comparative example is compared with Example 2, except that no ether lyase and lipase are added. The remaining components of the bio-based core material are the same as in Example 2; the reactive wall material used is the same as in Example 2.
[0133] The method for using the bio-based epoxy asphalt self-repairing microcapsules provided in this comparative example is the same as that in Example 2.
[0134] The performance test results of Comparative Example 1 are shown in Table 2:
[0135] Table 2 Test results of bio-based epoxy asphalt self-repairing microcapsule mixture in comparative example 1
[0136]
[0137]
[0138] As shown in Table 2, compared with Example 2, Comparative Example 1 did not add thermophilic etherase and Antarctic Candida lipase, which resulted in the inability to repair the ether bonds and ester bonds broken by aging of the epoxy resin. The epoxy bio-oil could only be used to fill and repair the micron-scale cracks, which had limited effect. As a result, the initial stiffness recovery rate, fatigue life recovery rate, and maximum bending-tensile strain recovery rate of the beam after the first repair were relatively low, which were only 72.4%, 65.6%, and 67.2%, respectively. Compared with Example 2, they were reduced by 20.7%, 21.6%, and 19.7%, respectively.
[0139] Comparative Example 2
[0140] The bio-based core material used in this comparative example is different from that in Example 2 in that glucose and ethanol are not added, and the remaining components of the bio-based core material are the same as those in Example 2; the reactive wall material used is the same as that in Example 2.
[0141] The method for using the bio-based epoxy asphalt self-repairing microcapsules provided in this comparative example is the same as that in Example 2.
[0142] The performance test results of Comparative Example 2 are shown in Table 3:
[0143] Table 3 Test results of bio-based epoxy asphalt self-repairing microcapsule mixture in comparative example 2
[0144]
[0145] As shown in Table 3, compared with Example 2, Comparative Example 2 did not add glucose and ethanol, and the auxiliary enzyme could not be replenished in time after the repair reaction was inactivated, and multiple repairs could not be achieved. As a result, while the first repair effect was equivalent to that of Example 2, the initial stiffness recovery rate, fatigue life recovery rate, and beam maximum bending strain recovery rate after the second and third repairs decreased significantly compared with Example 2, decreasing by 11.6%, 17.1%, 14%, and 27.4%, 27.2%, and 24.5%, respectively.
[0146] Comparative Example 3
[0147] The bio-based core material used in this comparative example is the same as that in Example 2; the reactive wall material used is different from that in Example 2 except that nanocellulose whiskers are not added, and the remaining components of the reactive wall material are the same as those in Example 2.
[0148] The method for using the bio-based epoxy asphalt self-repairing microcapsules provided in this comparative example is the same as that in Example 2.
[0149] The performance test results of Comparative Example 3 are shown in Table 4:
[0150] Table 4 Test results of the bio-based epoxy asphalt self-repairing microcapsule mixture in comparative example 3
[0151]
[0152] As shown in Table 4, compared to Example 2, Comparative Example 3, which used only chitosan and omitted the addition of nanocellulose whiskers, exhibited low overall stiffness in the reactive wall material. This resulted in the microcapsules breaking easily during the mixing and rolling stages, causing premature rupture of the bio-based core material and reducing the overall repair effectiveness. The repair effectiveness of all three tests decreased by approximately 6-8% compared to Example 2.
[0153] Comparative Example 4
[0154] The bio-based core material used in this comparative example is the same as that in Example 2; the reactive wall material used is different from that in Example 2, except that polyimide-nanocellulose whiskers are used instead of chitosan-nanocellulose whiskers, and the remaining components of the reactive wall material are the same as those in Example 2.
[0155] The method for using the bio-based epoxy asphalt self-repairing microcapsules provided in this comparative example is the same as that in Example 2.
[0156] The performance test results of Comparative Example 4 are shown in Table 5:
[0157] Table 5 Test results of the bio-based epoxy asphalt self-repairing microcapsule mixture in Comparative Example 4
[0158]
[0159] As shown in Table 5, compared to Example 2, Comparative Example 4 used polyimide-nanocellulose whiskers instead of chitosan-nanocellulose whiskers, resulting in a loss of the environmental response mechanism triggered by microcapsule rupture. This resulted in low microcapsule release efficiency during the repair phase, reducing the overall repair effect. The repair effect of all three tests decreased by approximately 5-8% compared to Example 2.
[0160] Comparative Example 5
[0161] The bio-based core material used in this comparative example is the same as that in Example 2; the reactive wall material used is different from that in Example 2 in that no stress inducer is used, and the remaining components of the reactive wall material are the same as those in Example 2.
[0162] The method for using the bio-based epoxy asphalt self-repairing microcapsules provided in this comparative example is the same as that in Example 2.
[0163] The performance test results of Comparative Example 5 are shown in Table 6:
[0164] Table 6 Test results of the bio-based epoxy asphalt self-repairing microcapsule mixture in Comparative Example 5
[0165]
[0166]
[0167] As shown in Table 6, compared to Example 2, Comparative Example 5 lacked the use of a stress-inducing agent. This resulted in fewer brittle nodes in the microcapsule wall material, an increase in the rupture stress threshold, and lower microcapsule release efficiency during the repair phase. Furthermore, the lack of a surface-modified stress-inducing agent also reduced the compatibility and dispersibility of the microcapsules in the epoxy asphalt system, reducing the overall repair effectiveness. The three repair results decreased by approximately 5-8% compared to Example 2.
[0168] Comparative Example 6
[0169] The bio-based core material used in this comparative example is different from that in Example 2 in that glycerol and trehalose are not added, and the remaining components of the bio-based core material are the same as those in Example 2; the reactive wall material used is the same as that in Example 2.
[0170] The method for using the bio-based epoxy asphalt self-healing microcapsules provided in this comparative example is compared with that in Example 2, except that P1 is not performed, and the bio-based epoxy asphalt self-healing microcapsules, epoxy resin component A, epoxy resin component B, aggregate and asphalt are directly mixed and stirred, and the remaining steps are the same as in Example 2.
[0171] The performance test results of Comparative Example 6 are shown in Table 7:
[0172] Table 7 Test results of bio-based epoxy asphalt self-repairing microcapsule mixture in comparative example 6
[0173]
[0174]
[0175] As shown in Table 7, compared to Example 2, Comparative Example 6 omitted the protective agents glycerol and trehalose, resulting in inactivation of the enzyme system in the bio-based core material when exposed to dryness or high temperatures, reducing the repair effect. Furthermore, Comparative Example 6 directly mixed and stirred the bio-based epoxy asphalt self-healing microcapsules, epoxy resin component A, epoxy resin component B, aggregate, and asphalt. This increased the mixing time of the microcapsules in the high-temperature environment, increasing the likelihood of premature rupture and further reducing the repair effect. Ultimately, the repair results of all three tests decreased by approximately 7-10% compared to Example 2.
[0176] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A bio-based epoxy asphalt self-repairing microcapsule, characterized in that: The self-repairing microcapsules include a bio-based core material and a reactive wall material; Calculated by weight, the bio-based core material includes: 8~10 parts of repair enzyme complex; 3-5 parts of auxiliary enzyme complex; 20-25 regeneration substrates; 10~15 parts of protective agent; The reactive wall material comprises: 20~25 parts of bio-based main wall materials; 1~5 parts stress inducer; 0.5~1 parts of surface modifier; 3~5 parts of cross-linking agent.
2. The bio-based epoxy asphalt self-repairing microcapsule according to claim 1, characterized in that: The repair enzyme complex is prepared by mixing ether lyase, lipase and epoxy bio-oil in a mass ratio of 1-2:1-2:10-20; The ether lyase is obtained by hydrophilic modification of thermophilic etherase; The lipase is derived from the lipase of Candida antarctica by lipophilic modification; the melting points of the ether lyase and lipase are 150-180°C; The epoxidized bio-oil is at least one of epoxidized soybean oil, epoxidized castor oil and epoxidized cottonseed oil; and the viscosity of the epoxidized bio-oil is 200 mPa·s to 500 mPa·s.
3. The bio-based epoxy asphalt self-repairing microcapsule according to claim 1, characterized in that: The coenzyme complex is formed by mixing the oxidized coenzyme and the artificial coenzyme in a mass ratio of 3-5:5-7; The oxidized coenzyme is at least one of nicotinamide coenzyme, flavin coenzyme and quinone coenzyme; the artificial coenzyme is at least one of artificial nicotinamide, phenazine methyl sulfate and artificial quinone coenzyme.
4. The bio-based epoxy asphalt self-repairing microcapsule according to claim 1, characterized in that: The bio-based main wall material has a thermal decomposition temperature greater than 250°C and is a composite system of chitosan and nanocellulose whiskers in a mass ratio of 4-5:0.8-1; The chitosan is modified by grafting alkyl chains with methyl methacrylate; the elastic moduli of the chitosan and the nanocellulose whiskers are 0.5 GPa to 1 GPa and 150 GPa to 200 GPa respectively.
5. The bio-based epoxy asphalt self-repairing microcapsule according to claim 1, characterized in that: The stress inducing agent is at least one of nano-silicon dioxide or nano-calcium carbonate treated with a surface modifier, with a content of 10-20wt% of the bio-based main wall material, an elastic modulus of 150GPa-200GPa, and a preset defect density of 10 4 ~10 6 pieces / cm 2 ; The surface modifier is at least one of a silane coupling agent and sorbitan oleate.
6. The bio-based epoxy asphalt self-repairing microcapsule according to claim 1, characterized in that: The particle size of the self-repairing microcapsules ranges from 100 μm to 200 μm; the thickness of the reactive wall material ranges from 1 μm to 2 μm, and the fracture stress ranges from 15 MPa to 60 MPa.
7. The bio-based epoxy asphalt self-repairing microcapsule according to claim 1, characterized in that: The regeneration substrate is a mixture of glucose and ethanol in a mass ratio of 6-8:2-4.
8. The bio-based epoxy asphalt self-repairing microcapsule according to claim 1, characterized in that: The protective agent is a mixture of glycerol and trehalose in a mass ratio of 2-3:1-2; The cross-linking agent is at least one of tea polyphenols, tannic acid or sodium tripolyphosphate.
9. The bio-based epoxy asphalt self-repairing microcapsule according to claim 1, characterized in that: The self-repairing microcapsules are formed by sequentially adding a bio-based core material solution, an emulsifier, and a cross-linking agent to a reactive wall material precursor solution, stirring the solution for reaction, and then freeze-drying the solution. The reactive wall material precursor liquid is formed by sequentially adding a stress inducer and a surface modifier into a bio-based main wall material and stirring the mixture.
10. A method for using bio-based epoxy asphalt self-repairing microcapsules, characterized in that: include: The self-repairing microcapsules are mixed evenly with the epoxy resin component A to obtain a microcapsule-epoxy resin premix; The aggregate, epoxy resin component B and asphalt are pre-mixed uniformly to obtain epoxy asphalt premix; The microcapsule-epoxy resin premix is added into the epoxy asphalt premix and mixed to form a bio-based self-repairing microcapsule epoxy asphalt mixture.